Pelatihan Manajemen Keuangan dan Pemasaran pada UKM Lebah Sempage melalui Pelatihan Akuntansi Sederhana dan Digital Marketing: Manajemen Keuangan dan Pemasaran pada UKM Lebah Sempage melalui Pelatihan Akuntansi Sederhana dan Digital Marketing - Febriana, Widia; Fahry; Anggriani, Rini; Komala, Rina; Fikri Rahman, Haikal; Ulya khae Roni , Izzatul (Jurnal Tiyasadarma, 2025)
Small And Medium Enterprises Play An Important Role In The Economic Development Of A Region, As They Have The Ability To Absorb Labor And Contribute To The Economy. In Lebah Sempage Village, Smes Face Challenges In Financial Management And Marketing, Which Hinders Their Growth And Expansion. This Study Aimed To Provide Financial Management And Digital Marketing Training To Smes In Sempage Bee Village To Improve Their Financial Performance And Increase Their Sales. The Training Program Consisted Of Several Stages, Including A Field Survey, Providing Training On Financial Reporting, Opening Market Networks Through Promotional Activities, And Offering Knowledge On Marketing Strategies To Increase Local Sales. The Financial Management Training Focused On The Use Of Digital Financial Reports, Which Help Sme Owners Accurately Record Their Sales, Purchases, And Expenses. The Digital Marketing Training Covered Topics Such As Creating Promotional Content And Utilizing Various Digital Platforms To Reach A Wider Audience.